El Excentrico, 1970-11-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
November 5, 1970 [5 de noviembre de 1970]. No volume or issue number. Cover has a photograph of Robero Ramirez (El Primroso) with two women and the headline, "San Jose's FAKIR turn on charm!"